Creativity Greenhouse: at-a-distance collaboration and competition over research funding - Schnädelbach, Holger; Sun, Xu; Kefalidou, Genovefa; Coughlan, Tim; Meese, Rupert; Norris, James; McAuley, Derek (Elsevier, 2016)
This paper describes the design and evaluation of a novel mechanism to develop research proposals and distribute funding: Creativity Greenhouse (CG). Building on an established funding sandpit mechanism for co-located participants, communication technologies and structures were designed to support similar activities at-a-distance. Given a particular topic, selected academic participants collaborate during an ideation phase, then form sub-groups around selected ideas to develop research proposals and compete for the available research funding. This paper details the motivations for developing a distributed approach, before describing our iterative design process and trials. We describe an iterative design and evaluation process to support at-a-distance ideation, group formation, and then competitive development of proposals in a shared virtual space, leading to the detailed evaluation of a full-scale CG event that resulted in the distribution of £1.85 Million of funding. This work contributes a novel, fully-developed mechanism to produce research projects, evaluated ‘In the Wild’. Our findings are explored with regards to distinctions and similarities between co-located and distributed events, participant well-being and pastoral care, and the capacity of technologies to mediate complex combinations of cooperative and competitive group work. Through this, we contribute knowledge of how to effectively support research funding events, and also to wider understanding of high-stakes, computer-mediated processes, that involve complex creative and social processes.